Corporate Criminal Responsibility in Environmental Crimes: a Case Study of Industrial Pollution - Kemmala Dewi; Abd Razak Musahib; Mustofa Ponco Wibowo (PT. Anagata Sembagi Education, 2025)
Criminal law enforcement against companies in environmental crime cases still faces significant challenges. Although Law Number 32 of 2009 concerning Environmental Protection and Management (PPLH Law) has regulated criminal sanctions for companies that pollute the environment, its implementation is still weak. The main factors that hinder the effectiveness of law enforcement include difficulties in proving criminal elements, weak capacity of law enforcement officials, and political and economic pressures that benefit polluting companies. In addition, corruption, overlapping authority between institutions, and inequality between regulations and implementation are the main obstacles in criminally ensnaring companies. The principles of strict liability and corporate criminal liability that are expected to ensnare polluting companies are still not applied optimally. Legal reform is needed to strengthen the effectiveness of environmental criminal law enforcement, including through increasing the capacity of law enforcement officers, improving regulations, and implementing stricter sanctions such as the revocation of business licenses. Information transparency, inter-agency coordination, and protection for whistleblowers must also be strengthened. With these steps, it is hoped that environmental law enforcement can be more effective in providing a deterrent effect to polluting companies, ensuring corporate criminal responsibility, and upholding the principles of environmental justice in Indonesia.